2013
DOI: 10.1007/s00592-013-0491-9
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional education and carbohydrate counting in children with type 1 diabetes treated with continuous subcutaneous insulin infusion: the effects on dietary habits, body composition and glycometabolic control

Abstract: Carbohydrate counting (CHC) in combination with nutritional education has been used to optimize the insulin dose in patients with type 1 diabetes (T1D). The aim of this study was to test the impact of CHC and nutritional education on changes in dietary habits, body composition and body fat distribution in children with T1D treated with insulin pumps (CSII). Twenty-five children with T1D and CSII were recruited and valuated at baseline and after 18 months of follow-up. They were trained in CHC and following sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 19 publications
2
26
0
2
Order By: Relevance
“…Evidence from both structured [27,28] and psychosocial [29] education interventions suggests that nutrition education can lead to improvements in dietary intake and guideline adherence among individuals with Type 1 diabetes. Furthermore, studies in Europe [30][31][32] have reported adoption of healthier diets with the receipt of nutrition recommendations as part of routine care, where routine care varied from a single, 5-day inpatient education programme in France [30] to meeting with a dietitian during routine outpatient medical consultations every 3 months [31] or twice per year in Italy [32]. There are several potential reasons why no consistent association was observed between diabetes nutrition therapy and dietary intake in the present sample of individuals with Type 1 diabetes in China.…”
Section: Results Indicate That Diabetes Nutrition Therapy In Chinamentioning
confidence: 99%
“…Evidence from both structured [27,28] and psychosocial [29] education interventions suggests that nutrition education can lead to improvements in dietary intake and guideline adherence among individuals with Type 1 diabetes. Furthermore, studies in Europe [30][31][32] have reported adoption of healthier diets with the receipt of nutrition recommendations as part of routine care, where routine care varied from a single, 5-day inpatient education programme in France [30] to meeting with a dietitian during routine outpatient medical consultations every 3 months [31] or twice per year in Italy [32]. There are several potential reasons why no consistent association was observed between diabetes nutrition therapy and dietary intake in the present sample of individuals with Type 1 diabetes in China.…”
Section: Results Indicate That Diabetes Nutrition Therapy In Chinamentioning
confidence: 99%
“…Isso reforça a necessidade de que a contagem de carboidratos e a flexibilidade alimentar inerente ao método seja pautada em escolhas saudáveis. Neste estudo, assim como no de Magliono et al, 36 os pacientes que aplicaram a contagem de carboidratos apresentaram melhora significativa nas concentrações de A1C, aumento no consumo de carboidratos e diminuição no consumo de gorduras e proteínas, sem que esse método de abordagem nutricional interferisse na distribuição da gordura corporal. Não há evidências suficientes para afirmar que a aplicação da contagem de carboidratos provoque mudanças antropométricas e de composição corporal, quer sejam positivas ou negativas.…”
Section: Discussionunclassified
“…Studies have shown that the use of an automated bolus calculator may assist patients with the complex calculations and provide additional benefits over manual carbohydrate counting in patients using CSII (Enander, Gundevall, Strongren, Chaplin, & Hanas, 2012;Schmidt, Schelde, & Nørgaard, 2014) and MDI (Anderson, 2009;Rabbone et al, 2014). However, not all studies reporting a benefit with carbohydrate counting included a control group making interpretation difficult (Dias et al, 2010;Lowe et al, 2008;Marigliano et al, 2013;Rossi et al, 2010;Samann, Muhlhauser, Bender, Kloos, & Muller, 2005). Conversely, other studies have shown no significant improvement in HbA1c with carbohydrate counting (Gilbertson et al, 2001;Laurenzi et al, 2011;Mitchell, Nowakowska, & Hurstt, 1990;Son, Efe, Son, Akalin, & Kebapci, 2014).…”
Section: Long-term Glycemic Control (Hba1c)mentioning
confidence: 90%